Video-assisted thoracic surgery left upper lobectomy with systematic lymphadenectomy - Lin, Zongwu; Xu, Songtao; Zhao, Junjie; Wang, Qun (Journal of Thoracic Disease; Vol 6, No 12 (December 31, 2014): Journal of Thoracic Disease, 2014)
A 43-year-old man was referred to our hospital after chest computed tomography revealed a 2.5-cm mixed ground-glass opacity peripherally in the left upper lobe of the lung. No metastasis or contraindication for surgery was found. Video-assisted thoracic surgery (VATS) left upper lobectomy was performed, and analysis of the intraoperative frozen section confirmed the diagnosis of adenocarcinoma. Subsequently, systematic lymphadenectomy was performed. By using this method, suction and harmonic scalpel were the only two major instruments needed throughout the operation. The use of suction ensures a clear view, and the harmonic scalpel functions as a combined dissector, grasper, and cutter, which helps avoid changing instruments during the surgery and saves time. Moreover, the use of this technique for three-port VATS lobectomy facilitates the conversion into single-port VATS if needed.